Pengaruh Media Mind Mapping terhadap Hasil Menulis Teks Deskripsi pada Siswa Kelas IV Sekolah Dasar - Sa'diah, Aila Rahmah; Indihadi, Dian; Rahayu Saputra, Erwin (Universitas Jambi, 2025)
ABSTRACT This study aims to improve students' descriptive text writing skills through the use of mind mapping media as an aid in the pre-writing stage. The method used in this study is a pre-experimental experiment with a one-group pretest-posttest design conducted with a pretest, treatment, and posttest. The research subjects consisted of 22 fourth-grade students of SDN 1 Gunungcupu. The results showed an increase in the average score from 8.73 in the pretest to 11.64 in the posttest. In addition, the lowest and highest scores also increased, from 5 and 12 in the pretest to 8 and 14 in the posttest. The normality test produced a significance value of 0.369 and 0.103 for the pretest and posttest, both of which were greater than 0.05, indicating that the data were normally distributed. Meanwhile, the results of the Paired Sample t-Test showed a significance value of 0.000 (less than 0.05), indicating a significant difference between the pretest and posttest results. Thus, it can be concluded that the use of mind mapping media has an effect on the descriptive text writing skills of fourth grade students.